2013
DOI: 10.1186/1479-5876-11-272
|View full text |Cite
|
Sign up to set email alerts
|

LARP1 predict the prognosis for early-stage and AFP-normal hepatocellular carcinoma

Abstract: BackgroundThe La-related protein 1 (LARP1) has been found to be a RNA binding protein and was related to spermatogenesis, embryogenesis and cell-cycle progression. The aim of this study was to investigate the prognostic value of LARP1 in hepatocellular carcinoma (HCC).MethodsLARP1 expression was examined in 15 HCC cell lines and 272 clinical specimens using real-time PCR, immunohistochemistry (IHC) and western blot analysis (WB). LARP1 expression was also studied in 6 paired HCC lesions and the adjacent non-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…Among other ribosomal-biogenesis regulating molecules, the RNA binding protein LARP1 was recently shown to promote the stability of mTOR mRNA and sustain downstream mTOR signaling, a mechanism that appears to correlate with cancer progression as shown in human specimens from cervical and non-small cell lung cancers [97]. Similar evidence has been also observed in hepatocellular carcinoma [98]. The anabolic and catabolic processes regulated by mTORC1 span from protein, ribosome, lipid and nucleotide biosynthesis to autophagy and cell survival, respectively.…”
Section: Introductionmentioning
confidence: 74%
“…Among other ribosomal-biogenesis regulating molecules, the RNA binding protein LARP1 was recently shown to promote the stability of mTOR mRNA and sustain downstream mTOR signaling, a mechanism that appears to correlate with cancer progression as shown in human specimens from cervical and non-small cell lung cancers [97]. Similar evidence has been also observed in hepatocellular carcinoma [98]. The anabolic and catabolic processes regulated by mTORC1 span from protein, ribosome, lipid and nucleotide biosynthesis to autophagy and cell survival, respectively.…”
Section: Introductionmentioning
confidence: 74%
“…As such, LARP1 mRNA was shown to be particularly up-regulated in liver cancer (Chen et al 2002;Wurmbach et al 2007;Roessler et al 2010). In addition, a recent study showed that LARP1 mRNA and protein levels were up-regulated in several hepatocellular carcinoma (HCC) cell lines as well as in HCC patients who concomitantly had a lower survival rate (Xie et al 2013), raising the possibility that LARP1 may serve as a biomarker for predicting the prognosis of HCC. Despite promising preclinical and early clinical results obtained with mTOR inhibitors, resistance of cancer cells to these treatments has been reported.…”
Section: Discussionmentioning
confidence: 96%
“…It plays a key role in embryogenesis, oogenesis, spermatogenesis, mitotic spindle formation, mitochondrial segregation, and cell cycle progression [2426]. Although LARP1 plays an important role in tumorigenesis and progression of cervical cancer, non-small cell lung cancer, HCC, and prostate cancer [10, 18, 27, 28], the biological function and prognostic value of LARP1 expression in human colon cancer are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LARP1 was shown to be overexpressed in cervical and non-small cell lung cancers, with increased expression correlated with cancer progression and poor prognosis [14]. As a promising biomarker, the expression of LARP1 is closely related to poor prognosis of early-stage and alpha-fetoprotein-normal hepatocellular carcinoma (HCC) patients [18]. Recently, it has been found that downregulation of LARP1 expression in endometrial cancer and lung cancer cell lines was associated with decreased cell proliferation [19].…”
Section: Introductionmentioning
confidence: 99%